Pentalogy of cantrell with single umbilical artery: a rare fetal anomaly - Meena, Raj Kumar; Meena, Veena (International Journal of Contemporary Pediatrics, 2016)
Pentalogy of cantrell (PC) is a rare syndrome having both specific ventral and dorsal midline defect, and rarely found to be associated with other anomalies. Most cases occur randomly for no apparent reason (sporadically). We report a 20 years old primigravida referred at 17 weeks 4 days of gestational age, for a fetal anomaly scan having an anterior abdominal wall defect in fetus. Ultrasound done, showed single live fetus gestational age of 18 weeks, with fetal heart, great vessels, stomach, and intestinal loops were found to be lying outside thoracic cavity. Fetal autopsy following termination of the pregnancy confirmed the presence of the malformations with single umbilical artery. Occurrence of both ventral and dorsal midline defects suggests that the timing of fetus insult would be between 14 to 18 days after conception when the splanchnic mesoderm (myocardium) and somatic mesoderm (sternum, abdominal wall, diaphragm and pericardium) is dividing.